Primary cutaneous alveolar rhabdomyosarcoma: Case report in a young adult - Beatriz Poliseli Cernescu; Mayara Teixeira Cruz; Cássio Rafael Moreira; Lígia Márcia Mário Martin; Nikolai Cernescu (Sociedade Brasileira de Dermatologia (SBD), 2020)
Sarcomas are rare and malignant mesenchymal neoplasms that mainly affect children and adolescents. Rhabdomyosarcoma, a subtype originating from skeletal muscle, is an uncommon condition in adults. It affects sites of unusual location, presents fast growth, and is challenging to treat. We report a case of a young adult with nodules in the left auricular lobe. The histopathological and immunohistochemical analysis confirmed the alveolar rhabdomyosarcoma, and treatment was conducted in association with Oncology.